Avaliação dos acidentes por serpentes do gênero Bothrops - Rodrigues, Elaine Cristina Araújo Medeiros de Souza (2018)
Introduction: For many years, snakebites have become one of the most neglected tropical diseases in the world. In Brazil, Bothrops snakes are responsible for the highest number of recorded cases. The venom of these snakes has actions: coagulant, proteolytic and hemorrhagic, which trigger local and systemic manifestations in the body of the victim. In these accidents, the effective diagnosis and the early administration of the antibotroic serum therapy are indispensable for neutralization of the poison and favoring a better prognosis for the injured. Objective: To evaluate the botrópico, epidemiological, clinical, laboratorial and possible repercussions after changes in the serotherapic treatment, of the cases reported in the Information Center and Toxicological Assistance, located in the city of Campina Grande -PB (CIATox-CG), in the period between August 2015 and July 2017. Methodology: A retrospective and comparative cross-sectional study was carried out. Two groups were established: a group composed of cases of botrópico accidents reported between August 2015 and July 2016, which were treated according to the Manual of Diagnosis and Treatments of Accidents by Poisonous Animals; and another group constituted by the cases registered between August 2016 and July 2017, which were submitted to the serotherapic treatment according to the new guidelines of Information Bulletin nº 25 of 2016 of the Ministry of Health. Data were collected based on the Individual Notification Form (SINAN / MS), and a questionnaire was prepared for the collection of complementary data regarding the examinations and serum therapy used. Subsequently, the data were organized into a spreadsheet of Microsoft Office Excel 2013 software and imported into the Statistical Package for Social Sciences software (SPSS 17.0). Statistical analyzes were then performed, such as frequency calculation and Mann-Whitney test to verify association between variables. Results: Of the 294 cases analyzed, there was a higher incidence of male patients, farmers and literates. The lower limbs were the most affected. The main local clinical manifestations presented were pain, edema and the systemic ones were headache and hemorrhagic alterations. Most cases were classified as mild. There were statistically significant differences in the change in serum therapy for 'total ampoules administered' (prior to changes in serum therapy, about nine ampules per accident were administered, and decreased to six currently) and 'days of hospitalization' (before with median from three to four days). Conclusion: The prevalence of coagulopathies and the need for additional serum therapy to normalize the clinical picture of the victims of botulent accidents indicate that the regional individuals pertinent to the endemic snake species in Paraíba should be considered in the estimation of the use of antivenom serum ampules by the services of health.